PENGUATAN KEARIFAN LOKAL BERBASIS BUDAYA MELALUI PENDIDIKAN KARAKTER PADA ANAK SEKOLAH DI DESA TENGANAN PAGRINGSINGAN KABUPATEN KARANGASEM - Ni Nyoman Metri (Guna Widya: Jurnal Pendidikan Hindu, 2021)
Potential growth in school children is carried out by teachers through character education by preserving local wisdom. Local wisdom is an intelligence possessed by certain ethnic groups, which is obtained through the experience of the ethnic struggling with their environment, Haryono (in Gunawan, 2015:17). When a society adapts to its environment, they develop a good wisdom in the form of knowledge or ideas, tools, combined with customary norms, cultural values, activities to manage the environment to meet the needs of their lives. Local wisdom is the result of a process of adaptation from generation to generation in a very long period of time to a natural environment in which to live. Local wisdom is generally in the form of oral and written in a social system of society. Local wisdom is closely related to geographical conditions or the natural environment with values that can be the main capital in building a community, with the characteristics of local wisdom including the ability to withstand external culture, to accommodate external cultural elements, to integrate elements of foreign culture into indigenous culture, to control culture, and to provide direction to cultural development. The strengthening of local wisdom in Tenganan Pagringsingan can be sustainable until now based on non-formal early character education, where parents in the villages of Tenganan Pagringsingan Banjar Kauh and Banjar Tengah have educated their children through speech and messages. which refers to the awig-awig of the traditional village of Tenganan where in the awig-awig there is an order that regulates the social life of the local community and sanctions against violations of the awig-awig.